Cytokines as a stressor: implications for depressive illness - Hymie Anisman; Shawn Hayley; Nicolas P. Turrin; Zul Merali (2002)
Stressful events have been implicated in the provocation of depressive illness. Inasmuch as immunological challenge, and particularly cytokine administration, engender neuroendocrine and central neurochemical changes reminiscent of those provoked by psychogenic stressors, it was suggested that immune activation may also contribute to affective illness. The present report provides a brief overview of the neurochemical sequelae of acute and repeated interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α) and IL-2 treatment, describes some of the synergisms associated with these treatments, as well as their potential interactions with psychogenic stressors. In addition, a discussion is provided concerning the fact that cytokines, like stressors, may have time-dependent proactive effects, so that re-exposure to the treatments provoke greatly augmented neurochemical changes (sensitization). Given that the effects of cytokines are evident within hypothalamic, as well as extrahypothalamic sites, including various limbic regions, it is suggested that cytokines may impact on emotional changes, including depression.